Opportunities and challenges of single-cell and spatially resolved genomics methods for neuroscience discovery - Bonev, Boyan; Castelo-Branco, Gonçalo; Chen, Fei; Codeluppi, Simone; Corces, M. Ryan; Fan, Jean; Heiman, Myriam; Harris, Kenneth; Inoue, Fumitaka; Kellis, Manolis; Levine, Ariel; Lotfollahi, Mo; et al. (Nature neuroscience, 2024)
Over the past decade, single-cell genomics technologies have allowed scalable profiling of cell-type-specific features, which has substantially increased our ability to study cellular diversity and transcriptional programs in heterogeneous tissues. Yet our understanding of mechanisms of gene regulation or the rules that govern interactions between cell types is still limited. The advent of new computational pipelines and technologies, such as single-cell epigenomics and spatially resolved transcriptomics, has created opportunities to explore two new axes of biological variation: cell-intrinsic regulation of cell states and expression programs and interactions between cells. Here, we summarize the most promising and robust technologies in these areas, discuss their strengths and limitations and discuss key computational approaches for analysis of these complex datasets. We highlight how data sharing and integration, documentation, visualization and benchmarking of results contribute to transparency, reproducibility, collaboration and democratization in neuroscience, and discuss needs and opportunities for future technology development and analysis.
Online veröffentlicht: 3. Dezember 2024
Gesehen am 07.04.2025